EVALUASI PELAYANAN DAN ADMINISTRASI POLRI DALAM PENGURUSAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR MASYARAKAT DI KANTOR SAMSAT PEKANBARU KOTA - Ardianto, Arif; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Progress of an area affected by the administrative system. The smooth administration of the area led to the smooth achievement of the goals and progress of the region itself. Service is at the core of the administration which requires the administrator to implement it properly in the organization of a region, particularly in the tax service office SAMSAT. Good service and the right will provide excellent results for the operation of the administration in the area. the importance of service and administration are given in Pekanbaru City SAMSAT office to the public by members of the National Police and assisted by local revenue offices. In these activities involve more local Revenue Office in terms of employment in particular SAMSAT payment, administration and tax services into a long procedure for the public to make payments where there are processes related to the police who should be separated in the submission to the public. Duties and obligations of the National Police in serving the community in which that has been listed in uu No. 02 of 2002.The purpose of this study to determine the evaluation of administrative services and police members in the management of public motor vehicle tax in Pekanbaru City SAMSAT office, in addition to inhibiting factors Knowing the evaluation of administrative services and police members in the motor vehicle tax administration office SAMSAT Pekanbaru City In research The author uses descriptive qualitative research method that gives an overview of the situation and analyze the data based on the field survey. In the study, which became the subject is SAMSAT Office of Police in the city of Pekanbaru, while the object of research is the evaluation of the police in providing services to its citizens. In this study there is a framework as a reference in developing a problem for researchers, service flow based on the principle of service according SutopoThe results of this study indicate that implementation of existing services need to be improved in terms of both performance and completeness of infrastructure and facilities in service delivery. So what is expected by society in Pekanbaru city will be realized. One of the issues that may need attention are eliminating intermediaries or brokers who relieved assigned services in the area of call centers services are very detrimental to society Pekanbaru. This causes loss of time and processing of different appliedKeyword : Evaluation, Administration, Services